2021
DOI: 10.24272/j.issn.2095-8137.2020.281
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomics highlights convergent evolution of energy metabolic pathways in group-living spiders

Abstract: Although widely thought to be aggressive, solitary, and potentially cannibalistic, some spider species have evolved group-living behaviors. The distinct transition provides the framework to uncover group-living evolution. Here, we conducted a comparative transcriptomic study and examined patterns of molecular evolution in two independently evolved group-living spiders and twelve solitary species. We report that positively selected genes among group-living spider lineages are significantly enriched in nutrient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
(31 reference statements)
0
0
0
Order By: Relevance
“…Cellular autophagy is equally crucial for maintaining energy homeostasis during periods of starvation [14]. Research has shown that the evolution of social spiders is linked to nutritional metabolism and autophagy, which regulate metabolic processes and mitigate the threat of cannibalism to ensure an adequate energy supply [15].…”
Section: Introductionmentioning
confidence: 99%
“…Cellular autophagy is equally crucial for maintaining energy homeostasis during periods of starvation [14]. Research has shown that the evolution of social spiders is linked to nutritional metabolism and autophagy, which regulate metabolic processes and mitigate the threat of cannibalism to ensure an adequate energy supply [15].…”
Section: Introductionmentioning
confidence: 99%